Novel insights into the role of luteinizing hormone in reproductive function : phenotypic analysis of luteinizing hormone receptor knockout mice - Pakarainen, Tomi (Turun yliopiston julkaisuja, ISSN 0355-9483, 2005)
Tiivistelmä: Luteinisoivan hormonin merkitys lisääntymistoimintoihin : luteinisoivan hormonin reseptori-poistogeenihiirien ilmiasun analysointi.
Keywords: luteinizing hormone; receptors, LH; spermatogenesis : drug therapy; estrogens; steroids : biosynthesis; ovarian follicle; ovary : growth & development; ovary : physiology; testis : growth & development; testis : physiology; testosterone; spermatogenesis; ovary; mice; lisääntyminen; muuntogeeniset eliöt; hiiret; estrogeenit; steroidit; sukupuolihormonit